Islam without extremes : a Muslim case for liberty - Akyol, Mustafa, 1972- (New York, NY : W.W. Norton, 2011)
From furious reactions to the cartoons of Prophet Muhammad to the suppression of women, news from the Muslim world begs the question: is Islam incompatible with freedom? With an eye sympathetic to Western liberalism and Islamic theology, Mustafa Akyol traces the ideological and historical roots of political Islam.
The beginnings. A light unto tribes -- The enlightenment of the Orient -- The medieval war of ideas (I) -- The medieval war of ideas (II) -- The desert beneath the iceberg -- The modern era. The Ottoman revival -- Romans, Herodians, and Zealots -- The Turkish march to Islamic liberalism -- Signposts on the liberal road. Freedom from the state -- Freedom to sin -- Freedom from Islam.
Includes bibliographical references (pages 291-329) and index.
Keywords: Islam and state; Secularism -- Islamic countries; Liberty -- Religious aspects -- Islam; Liberalism -- Islamic countries